The Influence of STEM (Science, Technology, Engineering, and Mathematics) Approaches on Learning Outcomes of Alternative Energy Subthemes - Rizqi Nur Syaadah; Teti Rostikawati; Resyi A. Gani (Journal of Social Science, 2023)
The purpose of this study was to improve learning outcomes in the alternative energy sub-theme by using a two-group design quasi-experimental research method at Selaawi State Elementary School. The subjects of this study were students in class III-A and III-B of Selaawi State Elementary School which consisted of 53 students. This research was conducted in the even semester of the 2020/2021 school year. The results showed that there was an influence of the STEM (Science, Technology, Engineering, and Mathematics) Approach on Learning Outcomes of the Alternative Energy Sub-theme. This can be seen from the average N-gain value in the experimental class group of 79 in the high category, and the average N-gain value in the control class is 57.77. Thus the results of testing the hypothesis that H0 is rejected and Ha is accepted because t_count> t_table is 9.5202 > 2.00758. Based on the results of this study, it can be concluded that this research shows that there is a positive effect of using the STEM approach.